Attenuation of Doxorubicin‐Induced Small Intestinal Mucositis by Pectins is Dependent on Pectin's Methyl‐Ester Number and Distribution. Issue 18 (7th August 2021) - Beukema, Martin; Jermendi, Éva; Koster, Taco; Kitaguchi, Kohji; de Haan, Bart J.; van den Berg, Marco Alexander; Faas, Marijke M.; Schols, Henk A.; de Vos, Paul
Abstract : Scope: Intestinal mucositis is a common side effect of the chemotherapeutic agent doxorubicin, which is characterized by severe Toll‐like receptor (TLR) 2‐mediated inflammation. The dietary fiber pectin is shown to prevent this intestinal inflammation through direct inhibition of TLR2 in a microbiota‐independent manner. Recent in vitro studies show that inhibition of TLR2 is determined by the number and distribution of methyl‐esters of pectins. Therefore, it is hypothesized that the degree of methyl‐esterification (DM) and the degree of blockiness (DB) of pectins determine attenuating efficacy on doxorubicin‐induced intestinal mucositis. Methods and Results: Four structurally different pectins that differed in DM and DB are tested on inhibitory effects on murine TLR2 in vitro, and on doxorubicin‐induced intestinal mucositis in mice. These data demonstrate that low DM pectins or intermediate DM pectins with high DB have the strongest inhibitory impact on murine TLR2‐1 and the strongest attenuating effect on TLR2‐induced apoptosis and peritonitis. Intermediate DM pectin with a low DB is, however, also effective in preventing the induction of doxorubicin‐induced intestinal damage. Conclusion: These pectin structures with stronger TLR2‐inhibiting properties may prevent the development of doxorubicin‐induced intestinal damage in patients undergoing chemotherapeutic treatment with doxorubicin. Abstract : Pectins with a low degree of methyl‐esterification (DM) or intermediate DM pectins with a high degree of blockiness have strong Toll‐like receptor (TLR) 2 inhibiting properties and prevent the induction of doxorubicin‐induced intestinal mucositis. Through inhibition of TLR2, these pectins prevent induction of doxorubicin‐induced apoptosis. A lower level of apoptosis together with barrier‐enhancing properties of pectins prevents bacterial translocation and subsequent intestinal damage.